2015
DOI: 10.1039/c5fo00689a
|View full text |Cite
|
Sign up to set email alerts
|

Lentinula edodes-derived polysaccharide rejuvenates mice in terms of immune responses and gut microbiota

Abstract: Aging is characterized by impaired immunity and unbalanced gut microbiota. Prebiotics have the capability to prevent or reverse age-related declines in health by modulating gut microbiota. Mushroom polysaccharides have been suggested to be potential prebiotics. However, their effects on the immunity and gut microbiota in aged mice have not been determined. This study firstly assessed the effects of a heteropolysaccharide L2 isolated from the fruit body of L. edodes on the immune response of aged mice, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 45 publications
4
35
0
Order By: Relevance
“…Recently, it was shown that lentinan can be effective for treating gut inflammation (4). It is also reported that polysaccharides extracted from Lentinula edodes can restore age-attenuated immune responses and reverse age-related alterations of gut microbiota compositions in mice (5). Furthermore, Lentinula edodes can be a source of ergosterol and ergothioneine (6).…”
Section: Importancementioning
confidence: 99%
“…Recently, it was shown that lentinan can be effective for treating gut inflammation (4). It is also reported that polysaccharides extracted from Lentinula edodes can restore age-attenuated immune responses and reverse age-related alterations of gut microbiota compositions in mice (5). Furthermore, Lentinula edodes can be a source of ergosterol and ergothioneine (6).…”
Section: Importancementioning
confidence: 99%
“…Mushroom polysaccharides exhibit advantages in immune‐modulating and anti‐tumor activities and have attracted intensive investigations to date (Ruthes et al, ). In a prior study, L2 exhibited anti‐ageing effects in the immune function and gut microbiota in aged mice (Xu et al, ). However, knowledge about the metabolic response to L. edodes ‐derived polysaccharide intervention in complex biological systems is still very limited.…”
Section: Discussionmentioning
confidence: 89%
“…Ageing processes are characterized by decline in immune responses (Xu et al, ), alterations of gut microbiota (Biagi et al, ), and changes in the nutrient sensing pathway (Lopez‐Otin, Blasco, Partridge, Serrano, & Kroemer, ). In particular, ageing in vivo decreases enzymatic activities participating in energy metabolism and the rate of oxidative phosphorylation resulting in an altered metabolic profile, which is shown as a metabolic shift from mitochondrial respiration to glycolysis in myoblasts (Paasuke et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations